IMPLEMENTASI MATERI BILANGAN DAN ARITMATIKA TERHADAP PESERTA DIDIK DALAM KURIKULUM SEKOLAH DASAR DI KOTA MEDAN - Meili, Maya; Safrida Napitupulu; Siti Khayroiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is motivated by two main factors. First, based on the 2022 PISA results, Indonesia ranked 72 out of 79 countries in mathematics with a proficiency rate of only 12%, far below the OECD average of 69%. Second, the average mathematics scores of elementary school students are often below the national minimum standards. This gap indicates a mismatch between curriculum content and student learning outcomes, influenced by factors such as teaching approaches, teacher competence, and the availability of learning media, particularly those supporting the understanding of number and arithmetic concepts, which are fundamental in mathematics learning at the elementary school level. The purpose of this study is to examine the implementation of number and arithmetic materials in the elementary school curriculum in Medan City and analyze their impact on the learning process and student outcomes. This study uses a qualitative descriptive method with data collected through classroom observations, interviews with teachers and students, and analysis of learning documents from several elementary schools in Medan City, conducted both offline and online. Curriculum. The results show that the implementation of number and arithmetic materials is generally in accordance with Indonesia’s current Most schools have adopted the Independent Curriculum, while some still apply the K13 Curriculum in selected classes. Implementation in lower grades tends to use concrete learning media, while upper grades focus more on abstract numerical concepts. The main challenges encountered include the limited availability of media and teaching aids, especially in lower grades, and disparities in student abilities that require greater teacher attention to ensure that learning objectives are achieved.